Multi-locus sequence data illuminate demographic drivers of Pleistocene speciation in semi-arid southern Australian birds (Cinclosoma spp.). Issue 1 (December 2016) - Dolman, Gaynor; Joseph, Leo
Abstract Background During the Pleistocene, shifts of species distributions and their isolation in disjunct refugia led to varied outcomes in how taxa diversified. Some species diverged, others did not. Here, we begin to address another facet of the role of the Pleistocene in generating today's diversity. We ask which processes contributed to divergence in semi-arid southern Australian birds. We isolated 11 autosomal nuclear loci and one mitochondrial locus from a total of 29 specimens of the sister species pair, Chestnut Quail-thrushCinclosoma castanotum and Copperback Quail-thrushC. clarum . Results A population clustering analysis confirmed the location of the current species boundary as a well-known biogeographical barrier in southern Australia, the Eyrean Barrier. Coalescent-based analyses placed the time of species divergence to the Middle Pleistocene. Gene flow between the species since divergence has been low. The analyses suggest the effective population size of the ancestor was 54 to 178 times smaller than populations since divergence. This contrasts with recent multi-locus studies in some other Australian birds (butcherbirds, ducks) where a lack of phenotypic divergence was accompanied by larger historical population sizes. Post-divergence population size histories ofC. clarum andC. castanotum were inferred using the extended Bayesian skyline model. The population size ofC. clarum increased substantially during the late Pleistocene and continued to increase through the Last Glacial Maximum and Holocene. The timing of this expansion across its vast range is broadly concordant with that documented in several other Australian birds. In contrast, effective population size ofC. castanotum was much more constrained and may reflect its smaller range and more restricted habitat east of the Eyrean Barrier compared with that available toC. clarum to the west. Conclusions Our results contribute to awareness of increased population sizes, following significant contractions, as having been important in shaping diversity in Australian arid and semi-arid zones. Further, we improve knowledge of the role of Pleistocene climatic shifts in areas of the planet that were not glaciated at that time but which still experienced that period's cyclical climatic fluctuations.